Corrigendum to: Economics of Chickpea Cultivation and Livelihood of Chickpea farmers in Drought-prone Region of Bangladesh - JSEA, Editor (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
Corrigendum to: Economics of Chickpea Cultivation and Livelihood of Chickpea farmers in Drought-prone Region of BangladeshDue to the article is not final yet and is worked with an updated version the author requests to unpublish the article from JSEA volume 9 (01) and considered submitting a newer version on the next JSEA volume. We apologize for any inconvenience to the reader.Keyword: Corrigendum